Analysis of the genetic basis of variation in cell sizes of natural isolates of the fission yeast Schizosaccharomyces pombe - KARARI, Kazhal (2017)
Investigating the relationship between sequence and phenotypic variation within a species is a powerful way of increasing our knowledge and understanding biological processes. Schizosaccharomyces pombe is an important, genetically tractable model for the analysis of the mechanisms of eukaryotic cell autonomous processes such as the cell cycle. However, all such work has been based on one approach and one strain which is commonly named the laboratory strain.(Brown et al., 2011) showed size variation in natural strains of S. pombe that isolated from around the world. Cell length increases progressively during the cell cycle of S. pombe and this observation thus suggested that there is polymorphic variation in machinery of cell cycle control. Many factors have been found to influence the cell cycle regulatory machine; one of these is the Wee1 kinase plays a particularly important role. Wee1 is an inhibitory regulator of the kinase Cdc2 that regulates the onset of mitosis and correspondingly the wee1 gene was originally identified by experimentally induced loss of function mutations which generated the eponymous phenotype. Here we use natural isolates of S. pombe to analyse the genetic architecture underlying variation in cell cycle control. In particular we examine the functional effect of wee1 polymorphism in two Brazilian isolates which have not previously been studied. First of all we use a cross between homothallic derivatives of these two isolates and a small collection of polymorphic markers in candidate genes to show that variation at or close to wee1 accounts for by 26% in the inherited component of the variance in cell size of the F1 offspring from these two Brazilian strains. The results from this preliminary genetic analysis were limited by the small number of markers that we used and by the fact that there was evidence for extensive non-Mendelian segregation in the cross. The cause of this non-Mendelian segregation was not known but it would limit the power of any further genetic analysis if widespread. We also address the functional consequence of 11 amino acid sequence variants of wee1 found within these Brazilian isolates and in 159 other isolates of S. pombe. We use both bioinformatics and experimental approaches. First, we looked for evolutionarily conserved residues in the sequences using fungal and yeast Wee1 protein sequences from FungiDB (http://fungidb.org/fungidb) and then aligned them at the EBI Muscle page (http://www.ebi.ac.uk/Tools/msa/muscle). We found that four polymorphic residues were conserved between S. pombe and one or more other yeast or fungi. We also used the Blink tool at SIFT (Sorting Intolerant from Tolerant) prediction program (http://sift.bii.a-star.edu.sg) to estimate the likely effect of the individual polymorphisms upon function. We found that both approaches of bio-informatics suggest that several of the substitutions were likely to have an effect upon protein function. Secondly, we analyse the functional consequences of wee1 sequence polymorphisms on cell length using experimental methods in the laboratory strain background. This experimental analysis showed that indeed some of the polymorphisms were functionally significant but that there was no simple relationship between the length of the cells of an isolate and the functional activity of wee1 on the laboratory strain background. In order to improve the precision and generality of the genetic analysis summarized above, we created a cross between two heterothallic derivatives of the Brazilian isolates. An initial check indicated that this largely solved the problems of non-Mendelian segregation displayed in the first cross and so we sized and sequenced 96 of the of the F1 segregants. We used R/qtl software to analyse the results and this confirmed the initial result that polymorphism within a gene at or close to wee1 is a major determinant of cell size in these natural isolates of S. pombe. This analysis also mapped a major QTL to chromosome 1 and to the mating type region. Identification of the variants within these regions responsible for these QTLs will require further bioinformatics analysis. Overall we have established that natural isolates of S. pombe can be used to identify variation in genes that affect evolutionarily conserved cell autonomous traits in S. pombe. This result significantly increases the power of S. pombe as an experimental system and offers the possibility of a new round of discoveries across a host of processes that lie at the heart of eukaryotic cell biology. If combined with field studies then this work should ultimately contribute to our understanding of the ecological factors that determine the relationship between standing variation within these different processes and genetic variation.